2017
DOI: 10.1007/s11523-017-0516-3
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Testosterone and White Blood Cell Count as a Predictive Factor of Overall Survival in Localized Prostate Cancer

Abstract: A high WBC and lymphocyte count combined with normal testosterone levels increases the overall mortality of patients treated with radiotherapy for localized prostate cancer within the first 6-7 years post-treatment. Validation in larger cohorts is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Up to now, leukocytes detected in the CellSearch cartridges were considered to constitute a non-specific carryover. The weak correlation between the leukocyte counts in the EpCAM-enriched samples and the leukocyte counts from the available complete blood counts (Table S1) rejects a plausible explanation that the leukocyte carryover reflects the total leukocyte count of patients, with the latter known to be associated with patients' clinical outcome in bladder, prostate, and non-small-cell lung cancers [44][45][46][47], as well as in colorectal cancer ( Table 1). That observation raised questions about the subtype of leukocytes isolated with the CTC kit, which either overexpress Fcγ receptors that bind to the IgG immunoglobulins of the anti-EpCAM ferrofluid, or express EpCAM.…”
Section: Discussionmentioning
confidence: 95%
“…Up to now, leukocytes detected in the CellSearch cartridges were considered to constitute a non-specific carryover. The weak correlation between the leukocyte counts in the EpCAM-enriched samples and the leukocyte counts from the available complete blood counts (Table S1) rejects a plausible explanation that the leukocyte carryover reflects the total leukocyte count of patients, with the latter known to be associated with patients' clinical outcome in bladder, prostate, and non-small-cell lung cancers [44][45][46][47], as well as in colorectal cancer ( Table 1). That observation raised questions about the subtype of leukocytes isolated with the CTC kit, which either overexpress Fcγ receptors that bind to the IgG immunoglobulins of the anti-EpCAM ferrofluid, or express EpCAM.…”
Section: Discussionmentioning
confidence: 95%
“…A systematic review by Claps and colleagues [ 45 ] investigated the association between total testosterone and overall mortality (including prostate cancer-specific mortality). In their meta-analysis of four cohort studies [ 38 , 39 , 46 , 47 ], the authors found little evidence of an association of total testosterone with overall mortality (HR = 1.03, 95% CI = 0.99–1.08, p = 0.19). Two of these cohort studies were not included our review as one study reported on men treated with ADT [ 46 ] and the other study reported on overall survival [ 47 ], not prostate cancer-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…In their meta-analysis of four cohort studies [ 38 , 39 , 46 , 47 ], the authors found little evidence of an association of total testosterone with overall mortality (HR = 1.03, 95% CI = 0.99–1.08, p = 0.19). Two of these cohort studies were not included our review as one study reported on men treated with ADT [ 46 ] and the other study reported on overall survival [ 47 ], not prostate cancer-specific survival. It is, therefore, evident that further research would benefit from examining testosterone concentrations in relation to prostate cancer-specific mortality as well as on measures of advanced prostate cancer (i.e., Gleason scores of ≥ 8, development of metastasises).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the number of neutrophils, and not the NLR, was an independent prognostic factor for overall survival [ 13 ]. In a follow-up study, we found that inflammatory markers are altered by testosterone: High levels of the sum of neutrophils and lymphocytes combined with normal testosterone levels increased the overall mortality [ 21 ]. Unfortunately, we only have very few patients with testosterone levels available to study the influence of testosterone on low- and intermediate-risk PCa.…”
Section: Discussionmentioning
confidence: 99%